Structural characterization of off-stoichiometric kesterite-type Cu2ZnGeSe4 compound semiconductors: from cation distribution to intrinsic point defect density. Issue 11 (8th February 2018) - Gunder, R.; Márquez-Prieto, J. A.; Gurieva, G.; Unold, T.; Schorr, S.
Abstract : The substitution of Ge 4+ for Sn 4+ in Cu2 ZnSn(S, Se)4 (CZTSSe) kesterite-type absorber layers for thin film solar cells has been proven to enhance the opto-electronic properties of the material. Abstract : The substitution of Ge 4+ for Sn 4+ in Cu2 ZnSn(S, Se)4 (CZTSSe) kesterite-type absorber layers for thin film solar cells has been proven to enhance the opto-electronic properties of the material. By cationic substitution, in general, the optical bandgap can be more readily designed for the purpose of bandgap engineering, and the substitution of Sn 4+ by Ge 4+, in particular, widens the optical bandgap such that it can be employed for both photovoltaics and solar fuel quarrying by photocatalytic water splitting. This work is an experimental study of intrinsic point defects in off-stoichiometric kesterite-type Cu2 ZnGeSe4 (CZGSe) by means of neutron powder diffraction. We revealed the existence of copper vacancies (VCu ), various cation antisite defects (CuZn, ZnCu, ZnGe, CuGe ) as well as interstitials (Cui, Zni ) in a wide range of off-stoichiometric polycrystalline materials synthesized by solid state reaction. In addition to the off-stoichiometry-type specific defects, Cu/Zn disorder is always present in the kesterite-type CZGSe phase. While compositional changes are clearly reflected by the tetragonal deformation c /2 a, the lattice parameters a and c seem differently responding to point defect types and concentration variations, respectively. The CuGe antisite defect which is known to greatly deteriorate the opto-electronic properties exists only in Cu-rich CZGSe, but appears already in CZGSe with Cu/(Zn + Ge) ≈ 1. Furthermore, we showed by diffuse reflectance hyperspectral imaging a widening of the energy bandgap in off-stoichiometric kesterite-type CZGSe with decreasing Cu/(Zn + Ge).